2013
DOI: 10.4048/jbc.2013.16.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Contrast-Enhanced Ultrasound Parametric Imaging in Breast Tumors

Abstract: PurposeThis study aimed to evaluate the diagnostic value of SonoLiver software for parametric imaging in breast tumors.MethodsContrast-enhanced ultrasound (CEUS) was performed in 216 breast lesions (113 malignant, 103 benign). The CEUS parameters were compared between benign and malignant lesions. The rise time, the time to peak, the mean transit time and dynamic vessel pattern (DVP) were analyzed using SonoLiver software.ResultsQuantitative analysis showed that the rise time was 16.52±4.15 seconds in the beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…In addition, there is a higher peripheral vessel distribution in malignant nodes, which is emphasized after contrast material administration, and the enhancement lasts for longer periods compared to benign nodes [19,20]. The diagnostic confidence in SLN characterization is improved using the CEUS [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a higher peripheral vessel distribution in malignant nodes, which is emphasized after contrast material administration, and the enhancement lasts for longer periods compared to benign nodes [19,20]. The diagnostic confidence in SLN characterization is improved using the CEUS [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Multiple parameters are used in CEUS and are mostly related to time that the contrast media interferes with the examined node. The rise time, the time to peak, the mean transit time and dynamic vessel pattern are the major useful values [10]. More and smaller vessels are identifiable in LNs after contrast media application and more accurate delineation of vascular architecture becomes possible [11].…”
Section: Methodsmentioning
confidence: 99%
“…Yuan et al [13] reported that parametric images enable the objective distinction of malignant and benign breast tumors, clarifying the degree of homogeneity or heterogeneity within the tumor. Although the assessment of CEUS images tends to be subjective, owing to improvements in the visibility with parametric imaging, the images may be more objective not only in the differentiation between benign and malignant but also in the assessment of the tumor extent and the tumor response after neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports that have utilized a color map gradation [10,12,13]. In a similar manner, we colored the map from red to purple per second.…”
Section: Parametric Imagesmentioning
confidence: 98%
See 1 more Smart Citation